CORRELATION OF BODY MORPHOMETRY AND UDDER VOLUME WITH MILK PRODUCTION IN ETTAWA CROSSBREED GOATS IN NUSA TENGGARA BARAT - Ni Made Andry Kartika; Abyadul Fitriyah; Yuni Mariani; Nefi Andriana Fajri (BRIN - Badan Riset dan Inovasi Nasional, 2026)
Observation of body size can be used as an identification of breeders as a selection criterion of dairy goats identify superior breeding stock and optimize milk production in Nusa Tenggara Barat, with potential implications for food security. The study aimed to determine the relationship between body size and udder volume with milk production of Etawa Crossbreed goat. This study was conducted at the experimental pen of Universitas Nahdlatul Wathan Mataram in Desa Ketangga Jeraeng, Lombok Timur, with twenty-five female Etawa Crossbreeds that were lactating. This study used a survey method and measurements of body length (BL), body height (BH), chest circumference (CC), udder volume (UV) and milk production (MP). Data were analyzed using correlation and linear regression analysis. The results showed that the average of BL = 72.76 cm, BH = 66.6 cm, CC = 73.24 cm, UV = 30.31 liters and MP = 327.76 ml / day. Body length and udder volume were moderately correlated with milk production (r = 0.40-0.59). While body height and udder volume had a strong correlation with milk production (r above 0.60). From the results, it can be concluded that body length, body height and udder volume had a significant effect on milk production, and there was a positive correlation with udder volume and milk production which was classified as a moderate correlation (r = 0.40-0.59).